BAPER POT: Processing Sugarcane Bagasse and Waste Paper into Flower Pots as a Solution to the Balance of Nature - Khansa Fikriyah Ziv; Zahrotus Sa'idah; Yesi Yuliani (Jurnal Integrasi Sains dan Quran, 2022)
The exaggerate we use paper, will sooner damaged the earth because its natural balance is disturbed. By recycling waste paper, you can help maintain the balance of nature. Indonesia is an agricultural country that has a lot of agricultural by-products in diverse. Sugarcane bagasse is one of the most widely produced agricultural wastes. Seeing the large number of sugarcane plantations around SMA Trensains Muhammadiyah Sragen and the waste of bagasse and waste paper produced every day, the researchers tried to utilize this waste into a more useful product, namely "Baper (bagasse and waste paper) Pot". This study used a qualitative descriptive method, while doing this research, researcher conducted several tests on the product.